2014
DOI: 10.1007/s10973-014-3979-9
|View full text |Cite
|
Sign up to set email alerts
|

The difference among the effects of high-temperature curing on the early hydration properties of different cementitious systems

Abstract: The difference among the effects of high-temperature curing on the early hydration properties of the pure cement, the binder containing fly ash, the binder containing GGBS, and the binder containing steel slag was investigated by determining the compressive strength, nonevaporable water content, hydration heat, and Ca(OH) 2 content. Results show that the order of the influence degrees of high-temperature on the early hydration of different binders is the binder containing GGBS [ the binder containing steel sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…That explains why the sorptivity coefficient of cement mixed with slag is half that of pure cement. In contrast, the content of hydration products of cement mixed with fly ash is lower due to the poor reactivity of fly ash [36] , which leads to showing a higher water absorption and low impermeability in the capillary water absorption test. However, research has shown that the sorptivity coefficient of cement blended with fly ash continues to decrease with the prolongation of curing time and the development of the pozzolanic reaction [37] .…”
Section: Influence Of Curing Methods On Water Absorption Of Cover Con...mentioning
confidence: 98%
“…That explains why the sorptivity coefficient of cement mixed with slag is half that of pure cement. In contrast, the content of hydration products of cement mixed with fly ash is lower due to the poor reactivity of fly ash [36] , which leads to showing a higher water absorption and low impermeability in the capillary water absorption test. However, research has shown that the sorptivity coefficient of cement blended with fly ash continues to decrease with the prolongation of curing time and the development of the pozzolanic reaction [37] .…”
Section: Influence Of Curing Methods On Water Absorption Of Cover Con...mentioning
confidence: 98%
“…This is more pronounced for the GGBS, which is more sensitive to high temperatures than other mineral admixtures and cement. Additionally, the hydration degrees of the GGBS and steel slag increase dramatically at higher temperatures [18][19][20]. Additionally, the hydration heat of the GGBS is so large that the hydration heat of the binder containing 17-40% fine GGBS is greater than that of plain cement at room temperature, and the hydration heat of the binder containing 30-50% GGBS is close to or even higher than that of plain cement at 60 ∘ C [20,21].…”
Section: Hydration Heat and Adiabatic Temperature Rise Figures 2(a) mentioning
confidence: 99%
“…Correspondingly, the concrete containing mineral admixtures usually achieves a lower early strength compared with the plain cement concrete [33,34]. However, the hydration degree of mineral admixtures increases significantly with the increase of curing temperature and steam curing time at early ages, which contributes to the strength development of concrete [35][36][37][38]. Therefore, steam curing is an effective method to improve the strength of concrete containing mineral admixtures at early ages [39][40][41].…”
Section: Introductionmentioning
confidence: 99%